2010
DOI: 10.1017/s1461145710000702
|View full text |Cite
|
Sign up to set email alerts
|

Oleamide administered into the nucleus accumbens shell regulates feeding behaviour via CB1 and 5-HT2C receptors

Abstract: The central nervous system control of food intake has been extensively studied, hence, several neurotransmitter systems regulating this function are now clearly identified, for example, the endocannabinoid and serotoninergic systems. The former stimulates feeding while the latter inhibits it. Oleamide (Ole) is a cannabimimetic molecule affecting both systems. In this work, we tested the orexigenic and anorectic potential of Ole when administered into the nucleus accumbens shell (NAcS), a brain region that has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…In contrast, 5‐HT 4 receptor antagonism in the NAc using RS39604 induces hyperphagia in fed but not food‐deprived mice (7). In addition, intra‐accumbal application of the 5‐HT 2A/2C receptor antagonist ketanserin stimulates food intake in rats (30). Thus, although the association between the 5‐HT system and feeding regulation previously has focused largely on homeostatic regulation in the hypothalamus (31), there is evidence for a role of these receptors in regulating reward aspects of feeding behavior, which results from the present study supports.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 5‐HT 4 receptor antagonism in the NAc using RS39604 induces hyperphagia in fed but not food‐deprived mice (7). In addition, intra‐accumbal application of the 5‐HT 2A/2C receptor antagonist ketanserin stimulates food intake in rats (30). Thus, although the association between the 5‐HT system and feeding regulation previously has focused largely on homeostatic regulation in the hypothalamus (31), there is evidence for a role of these receptors in regulating reward aspects of feeding behavior, which results from the present study supports.…”
Section: Discussionmentioning
confidence: 99%
“…The current experiments add to a growing literature that suggests that serotonergic signaling within the nucleus accumbens serves important and diverse roles in food-directed motivation [15, 23, 34, 35, 41]. Previous research has suggested that the hypophagic actions of systemic serotonergic agonists are primarily mediated by actions on hypothalamic circuitry involved in the homeostatic regulation of energy balance, with secondary actions on hindbrain circuitry involved in the sensory evaluation of foods [8, 20, 28, 29].…”
mentioning
confidence: 82%
“…Due to the fact that extensive scientific literature has supported the endocannabinoid system (eCBs) as a food ingestion modulator, the phyto and synthetic cannabinoids seem to be useful to affect such a function (Koch, 2001;Martínez-González et al, 2004;Méndez-Díaz et al, 2012;Merroun et al, 2009;Pérez-Morales et al, 2012;Soria-Gómez et al, 2010). In this context, it is now known that CB1R antagonists reduce food intake thereby promoting weight loss.…”
Section: Introductionmentioning
confidence: 99%